2020
DOI: 10.1017/jog.2020.48
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental microseismicity on detection and interpretation of small-magnitude events in a polar glacier setting

Abstract: Abstract Glacial environments exhibit temporally variable microseismicity. To investigate how microseismicity influences event detection, we implement two noise-adaptive digital power detectors to process seismic data from Taylor Glacier, Antarctica. We add scaled icequake waveforms to the original data stream, run detectors on the hybrid data stream to estimate reliable detection magnitudes and compare analytical magnitudes predicted from an ice crack source model. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…The InSight mission to Mars are able to detect more events during the evening hours than during the day when winds are increased (Giardini et al., 2020). Previous terrestrial studies on glaciers have also shown that microseismicity can affect the detection of other events (C. G. Carr et al., 2020). C. G. Carr et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The InSight mission to Mars are able to detect more events during the evening hours than during the day when winds are increased (Giardini et al., 2020). Previous terrestrial studies on glaciers have also shown that microseismicity can affect the detection of other events (C. G. Carr et al., 2020). C. G. Carr et al.…”
Section: Discussionmentioning
confidence: 98%
“…C. G. Carr et al. (2020) shows how modifications to the standard STA/LTA algorithm by using a noise‐adaptive detector can improve detection and reduce bias in detection statistics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The L‐22 seismometers have a natural or corner frequency of 2 Hz, and for our installation the Nyquist frequency was 100 Hz (sample rate: 200 Hz). The Rayleigh detector used in this study as well as the STA/LTA detectors from our previous study (Carr et al., 2020) implement (2.5, 35) Hz bandpass filters. This filter band is consistent with other Rayleigh‐wave icequake studies (e.g., Carmichael et al., 2015; Hudson et al., 2020; Linder et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The term ρA u(ξ 0 ) β 2 represents the elastic energy released by volumetric crack growth. Such sources are common in seismogenic hydrofracture events within glaciers (Carr et al, 2020;Taylor-Offord et al, 2019) and ice sheets (Carmichael et al, 2015).…”
Section: A Physical Source Of a Screening Errormentioning
confidence: 99%